(untitled) (Third Sector Social Economic Review, 2024)
The study aims to examine the relationship between non-performing loans, a crucial measure of banks’ asset quality, and key financial indicators. It tries to offer insights that can assist market participants in making informed forecasts based on the findings. The study encompasses the years 2010-2019. Financial indicators tend to worsen when markets are disrupted by extraordinary circumstances, which can make them unreliable for predicting normal periods. Following the 2008 global crisis, the Turkish economy went through a phase of stable fluctuations in macro and micro data until the end of 2019, when the initial indications of COVID-19 emerged. Although COVID-19 restrictions have been lifted, the lingering economic impact of the pandemic is anticipated to persist for the foreseeable future. As a result, banks’ asset management is expected to gradually return to pre-pandemic levels. Understanding the ratio of gross non-performing loan stock to total loans is crucial in assessing a bank’s asset quality. For this study, we analyzed data from January 2010 to December 2019, a period characterized by stable global markets. The data we used includes return on average assets, average TL deposit rate up to 3 months, and the ratio of total liabilities to total equity. It aims to provide a fresh perspective on the factors contributing to the average non-performing loan ratio of deposit banks in Turkey. Therefore, the goal is to provide a perspective on future strategies concerning non-performing loans. Based on the analyses, it is observed that the return on average assets and the ratio of liabilities to equity have a negative and significant relationship with the total non-performing loan (NPL) ratio. On the other hand, the average time deposit rate up to 3 months shows a significant and positive relationship with the average NPL ratio. The results are analyzed considering various economic theories such as market discipline, moral hazard, adverse selection, and bad management. The findings are anticipated to make a valuable contribution to the future strategies of banks, with potential implications for the management of non-performing loans during periods of low global risks.